Testosterone improves muscle fiber asset and exercise performance in a metabolic syndrome model. Issue 2 (May 2020) - Sarchielli, Erica; Comeglio, Paolo; Filippi, Sandra; Cellai, Ilaria; Guarnieri, Giulia; Guasti, Daniele; Rapizzi, Elena; Rastrelli, Giulia; Bani, Daniele; Vannelli, Gabriella; Vignozzi, Linda; Morelli, Annamaria; et al.
Abstract : Lifestyle modifications, including physical exercise (PhyEx), are well-known treatments for metabolic syndrome (MetS), a cluster of metabolic and cardiovascular risk factors often associated to hypogonadism. Given the trophic role of testosterone on skeletal muscle (SkM), this study was aimed at evaluating the effects of testosterone treatment on SkM metabolism and exercise performance in male rabbits with high-fat diet (HFD)-induced MetS. HFD rabbits, treated or not with testosterone (30 mg/kg/week) for 12 weeks, were compared to regular diet animals (RD). A subset of each group was exercise-trained for 12 weeks. HFD increased type-II (fast, glycolytic) and decreased type-I (slow, oxidative) muscle fibers compared to RD as evaluated by RT-PCR and histochemistry. Testosterone reverted these effects, also inducing the expression of mitochondrial respiration enzymes and normalizing HFD-induced mitochondrial cristae reduction. Moreover, testosterone significantly increased the expression of myogenic/differentiation markers and genes related to glucidic/lipid metabolism. At the end of the PhyEx protocol, when compared to RD, HFD rabbits showed a significant reduction of running distance and running time, while testosterone counteracted this effect, also decreasing lactate production. In the trained groups, muscle histology showed a significant reduction of oxidative fibers in HFD compared to RD and the positive effect of testosterone in maintaining oxidative metabolism, as also demonstrated by analyzing mitochondrial ultrastructure, succinate dehydrogenase activity and ATP production. Our results indicate that testosterone could be useful to promote oxidative muscle metabolism altered by MetS, thus improving exercise performance. Conversely, testosterone administration to otherwise eugonadal rabbits (RD) only increased muscle fiber diameter but not endurance performance.